2013
DOI: 10.1016/j.neuron.2013.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Anchored SNAREs Lacking Transmembrane Regions Fully Support Membrane Fusion during Neurotransmitter Release

Abstract: SUMMARY Synaptic vesicle fusion during neurotransmitter release is mediated by assembly of SNARE- and SM-protein complexes composed of syntaxin-1, SNAP-25, synaptobrevin-2/VAMP2, and Munc18-1. Current models suggest that SNARE-complex assembly catalyzes membrane fusion by pulling the transmembrane regions (TMRs) of SNARE proteins together, thus allowing their TMRs to form a fusion pore. These models are consistent with the requirement for TMRs in viral fusion proteins. However, the role of the SNARE TMRs in sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
115
5
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 53 publications
12
115
5
3
Order By: Relevance
“…In these lines, these data agree with a report showing that addition of the yeast HOPS complex, which includes the SM protein VPS33, restores complete fusion in a liposome-based fusion reaction containing reconstituted lipid-anchored v-SNARE, Nyv1p (27). A general role for SM proteins in supporting fusion by lipid-anchored SNAREs could also explain how the expression of lipid-anchored neuronal SNAREs can restore neurotransmitter release in Stx1 or Vamp2 knockout cultured neurons (30).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In these lines, these data agree with a report showing that addition of the yeast HOPS complex, which includes the SM protein VPS33, restores complete fusion in a liposome-based fusion reaction containing reconstituted lipid-anchored v-SNARE, Nyv1p (27). A general role for SM proteins in supporting fusion by lipid-anchored SNAREs could also explain how the expression of lipid-anchored neuronal SNAREs can restore neurotransmitter release in Stx1 or Vamp2 knockout cultured neurons (30).…”
Section: Discussionsupporting
confidence: 90%
“…If lipid-anchored STX11 mainly promotes incomplete fusion, how can it be essential for degranulation and cell-mediated cytotoxicity in CTLs and NK cells? A recent study has shown that lipid-anchored STX1 mediates synaptic vesicle fusion when expressed in cultured neurons (30), whereas in vitro fusion assays show that it mainly promotes incomplete fusion events (23,25,26). This finding could indicate that additional factors may facilitate the transition from incomplete to complete fusion in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Cpx was present throughout neurons, there was a preference for synaptic localization ( Fig. 2 A and C fused to the C-terminal palmitoylated sequence of cysteine-string protein-α (CSPα), a sequence that targets synaptic vesicles (46); and Cpx 1-86-CAIM is a chimera of Cpx fused to the C-terminal isoprenylation sequence (CAIM) that targets the plasma membrane (28). Immunocytochemistry experiments, similar to above, were again performed in lentivirus-infected neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors can contribute to lowering the energy barrier for two apposed membranes to rearrange their bilayers for fusion: (i) the physical force of membrane deformation deriving from trans-SNARE complexes forming continuous α-helices between their SNARE and transmembrane domains (42) [the initial concept that the energy for fusion derives entirely from forming a continuous α-helix between SNARE and transmembrane domains has been questioned by observations that transmembrane domains can be replaced by lipidic anchors for yeast vacuole fusion (43) or neuronal fusion (44)]; (ii) the docking of membranes in close proximity (45,46); (iii) the membrane bending that surrounds an extended region of membrane contact, driven by tethers (47); (iv) the enrichment of small headgroup lipids that can more readily fit into the nonbilayer lipidic structures of hemifusion and fusion intermediate states (25,34); and (v) localized (e.g., trans-SNARE-associated) additional proteins or other factors that can bind to lipids or insert into membranes to promote nonbilayer transitions. The latter includes Ca 2+ -triggered insertion of synaptotagmin at the neuronal synapse (48) and Sec17 for intracellular fusion.…”
Section: Discussionmentioning
confidence: 99%